Comparing various thixotropic models and their performance in predicting flow behavior of treated tailings - Talmon, AM; Meshkati, E; Nabi, M; Simms, P; Nik, RM (Paste 2023: 25th International Conference on Paste, Thickened and Filtered Tailings, 2023)
Treated tailings are known for their thixotropic rheological characteristics under flow, i.e. strength loss with time under constant shear rate, and strength gain at rest. Understanding and accurately quantifying the time-dependency of strength in treated tailings is crucial to sediment management operations such as mixing, pumping, hydraulic transport, flow and deposition. The are several thixotropic models available in the literature. This paper sheds light on the similarities and differences of representative thixotropic models and their pros and cons. Particular attention is paid to the model’s limitations/advantages in flow modelling. The performance of the models in predicting the flow behaviour of flocculated mature fine tailings (f-MFT) down a deposit’s beach is investigated. Particularly the free-surface profile is affected, which will have many practical implications for deposit management.